A brief reconnaissance of thee Chiapas Municipalities - Peterson, Fredrick A.
Preparing for the research -- Background to the servey and Región -- Reconnaissance in the Ocozocoautla, Jiquipilas, and Cintalapa municipalities -- Annual report 1958: reconnaissance of the la venta and cintalapa rivers -- A short trip along the la venta river canyon, 1959 -- A census of western Chiapas sites -- Notes on the culture history of western Chiapas.